Chronic kidney disease in public renal practices in Queensland, Australia, 2011–2018. Issue 12 (9th October 2022) - Hoy, Wendy E.; Wang, Zaimin; Zhang, Jianzhen; Diwan, Vishal; Cameron, Anne; Venuthurupalli, Sree K.; Fassett, Robert G.; Chan, Samuel; Healy, Helen G.; Tan, Ken‐Soon; Baer, Richard; Mallett, Andrew J.; et al.
Abstract: Aim: To describe adults with (non‐dialysis) chronic kidney disease (CKD) in nine public renal practice sites in the Australian state of Queensland. Methods: 7, 060 persons were recruited to a CKD Registry in May 2011 and until start of kidney replacement therapy (KRT), death without KRT or June 2018, for a median period of 3.4 years. Results: The cohort comprised 7, 060 persons, 52% males, with a median age of 68 yr; 85% had CKD stages 3A to 5, 45.4% were diabetic, 24.6% had diabetic nephropathy, and 51.7% were obese. Younger persons mostly had glomerulonephritis or genetic renal disease, while older persons mostly had diabetic nephropathy, renovascular disease and multiple diagnoses. Proportions of specific renal diagnoses varied >2‐fold across sites. Over the first year, eGFR fell in 24% but was stable or improved in 76%. Over follow up, 10% started KRT, at a median age of 62 yr, most with CKD stages 4 and 5 at consent, while 18.8% died without KRT, at a median age of 80 yr. Indigenous people were younger at consent and more often had diabetes and diabetic kidney disease and had higher incidence rates of KRT. Conclusion: The spectrum of characteristics in CKD patients in renal practices is much broader than represented by the minority who ultimately start KRT. Variation in CKD by causes, age, site and Indigenous status, the prevalence of obesity, relative stability of kidney function in many persons over the short term, and differences between those who KRT and die without KRT are all important to explore. Summary at a glance: This profile of CKD in public renal practices in Queensland, the first in any Australian state, exposes a much broader spectrum of characteristics than represented by those who ultimately start KRT, major variations in weightings of causes by age group, Indigenous status and practice site, strong links to obesity, and short‐term stability of renal function in many persons, all of which can influence design and evaluation of intervention strategies and inform public health policy.